SHINTOISM: NATURE'S OWN RELIGION - Kobayashi, Akiko (Journal of Dharma, 2001)
Japan is a nation of islands that are strewn in the Pacific Ocean, and is a country of mountain ranges, which run from North to South traversing the archipelago. The sources of its rivers that flow like a network Of blood vessels lie in these mountain ranges. The island nation of Japan is a land of lakes, forests and water sources, and a land of rice cultivation.